Given f(x) = 3(x − 4)2

𝑓
(
𝑥
)

=

3
(
𝑥



4
)
2
what is f(3)?

Show your work below

(1 point)
f(3)=
𝑓
(
3
)
=
(3)=3(3−4)2 Substitute in for x

f(3)=
𝑓
(
3
)
=
(3)=3(−1)2 Simplify the parenthesis

f(3)=
𝑓
(
3
)
=
(3)=3(1) Square the parenthesis

f(3)=
𝑓
(
3
)
=
3 Multiply

1 answer

Let's calculate \( f(3) \) step by step using the function \( f(x) = 3(x - 4)^2 \).

  1. Substitute \( x = 3 \) into the function: \[ f(3) = 3(3 - 4)^2 \]

  2. Simplify the expression inside the parentheses: \[ f(3) = 3(-1)^2 \]

  3. Square the value: \[ f(3) = 3(1) \]

  4. Multiply: \[ f(3) = 3 \]

Thus, the value of \( f(3) \) is \( \boxed{3} \).